The immunoglobulin γ marker 17 allotype and KIR/HLA genes prevent the development of chronic hepatitis B in humans - Di Bona, Danilo; Pandey, Janardan P.; Aiello, Anna; Bilancia, Massimo; Candore, Giuseppina; Caruso, Calogero; Colomba, Claudia; Duro, Giovanni; Ligotti, Mattia Emanuela; Macchia, Luigi; Rizzo, Sergio; Accardi, Giulia (Immunology, 2020)
Summary Hepatitis B virus (HBV) infection causes a self‐limiting disease in most individuals. However, < 10% of infected subjects develop a chronic disease. Genetic host variability of polymorphic genes at the interface of innate and acquired immunity, such as killer immunoglobulin‐like receptors (KIR), their human leucocyte antigen (HLA) and IgG allotypes (GM), could explain this different clinical picture. We previously showed a protective role of the KIR2DL3 gene for the development of chronic hepatitis B (CHB), and a detrimental role of the KIR ligand groups, HLA‐A‐Bw4 and HLA‐C2. We have expanded the previous analysis genotyping patients for GM23 and GM3/17 allotypes. The comparison of the patients with CHB with those who resolved HBV infection showed that the presence of GM17 allele virtually eliminated the risk of developing CHB (OR, 0·03; 95% CI, 0·004–0·16; P < 0·0001). In addition, the combination of GM17, KIR2DL3, HLA‐A‐Bw4 and HLA‐C2 was highly sensitive to predict the outcome of HBV infection. Logistic regression model to predict CHB development in the complete case database (n = 88).